Acute Coronary Syndrome – Exploring the Evidences Clinical Pharmacist Driven Cardiac Review - Alam, Aftab; Wadhwa, Tarun; Hassan, Elwaleed (Indian Journal of Pharmacy Practice)
Acute Coronary Syndrome is the most common type of coronary artery disease. Coronary artery disease and acute coronary syndrome together responsible for approx. 7 million deaths which accounts for around half of the global burden. World Health Organization report exemplified that 17.9 million deaths occurred in 2016 due to cardiovascular diseases which represents 31% of all global deaths. Known family history, age, male gender, hypercholesterolemia, diabetes mellitus, hypertension, lack of physical activity, abdominal obesity, cigarette smoking, psychosocial factors, consumption of too much alcohol and consumption of less fruits, vegetables and polyunsaturated fatty acids are some of the risk factors associated with coronary artery disease. Patients’ sign and symptoms, past medical history, ECG changes and determination of cardiac markers (Troponin and CK MB) are used to stratify patients into low, medium or high risk of death or MI, likelihood of failure of pharmacotherapy and need for immediate coronary angiography or percutaneous coronary intervention. For the management of acute coronary syndrome, cardiac drugs are recommended in addition to surgical interventions with specific goals for short and long term of treatment. Cardiac drugs need to be used cautiously in patients with coronary thrombosis as these category of drugs are responsible for increased incidence of adverse drug reactions thereby affecting the patient’s health status and economic condition. Therapeutic interventions like smoking cessation, managing dyslipidaemia and controlling blood pressure not only prevent coronary artery disease but also delays its progression and complications.
Keywords: Acute Coronary Syndrome; Adverse Drug Events; Adverse Drug Reactions; Cardiac Drugs; Coronary Artery Disease; Ischemic Heart Disease; Risk Factors; World Health Organization.